Activity limitations and subjective well-being after stroke. (29th August 2017) - Zahuranec, Darin B.; Skolarus, Lesli E.; Feng, Chunyang; Freedman, Vicki A.; Burke, James F.
Abstract : Objective: As limitations in activities of daily living are major components of many stroke outcome scales, we examined how well activity limitations predicted subjective well-being among stroke survivors in a nationally representative survey. Methods: Individuals with a self-reported history of stroke were identified from the National Health and Aging Trends Study. Subjective well-being (primary outcome) was assessed with a validated 7-item measure (higher = greater well-being) assessing emotions (cheerful, bored, full of life, and upset) and self-realization (purpose in life, self-acceptance, and environmental mastery). Activity limitations were defined by the receipt of help in any of 11 activities of daily living/instrumental activities of daily living. Multivariable linear regression assessed predictors of well-being including medical, physical, cognitive, psychological, and environmental factors. Results: A total of 738 stroke survivors age 65 or older were included (57% female, 9% African American, 6% Hispanic). Activity limitations were modestly associated with well-being after adjusting for demographic characteristics and availability of assistance (estimate −0.49, 95% confidence interval −0.61 to −0.37). However, in the fully adjusted model ( R 2 = 0.28), neither activity limitations nor physical capacity was associated with subjective well-being. Predictors of lower well-being in the final model included depressive symptoms, chewing/swallowing problems, pain that limited activity, and restricted participation in valued life activities. Income and executive function were modestly associated with improved well-being, while comorbidities and communication technology access were not associated. Conclusions: Activity limitations were not associated with stroke survivors' subjective well-being after adjustment for other factors. While some predictors of well-being after stroke were identified, the determinants of well-being remained largely unexplained.